Penetapan Kadar Paracetamol dalam Jamu di Kota Pontianak Menggunakan Instrumen Spektrofotometri UV-Vis - Fajar Nugraha; Hadi Kurniawan; Iga Yastiara (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Jamu is a traditional medicine used for generations in Indonesia. There are many regulations for jamu in Indonesia, one of which is the Regulation of the Minister of Health number 7 of 2012. The Minister of Health regulates the prohibition of distribution of jamu containing medicinal chemicals (BKO) that can endanger health. However, there are still many herbs containing BKO circulating in Indonesia, one of which is paracetamol. This study aims to verify the analytical method and measure the levels of paracetamol of jamu in Pontianak City, West Kalimantan. The verification of the analytical methods in this study is the measurement of linearity, accuracy, precision, Limit of Detection (LOD), and Limit of Quantification (LOQ). 3 (three) samples with different brands and indications were obtained through purchases from online shops. UV-Vis spectrophotometry used as a quantitative analytical instrument. The results of the linearity test obtained an r value of 0.999 and an r2 value of 0.999 which met the requirements of ICH, SNI, AOAC, and Eurachem. The results of the accuracy test have a %recovery range of 97.1986-102.2856% which meets the AOAC requirements. The results of the precision test have a %RSD range of 1.8197-7.7966% which meets the AOAC and Horwitz requirements. The results of the LOD calculation are 0.3273 ppm and the LOQ value is 0.9918 ppm. The results of the analysis using UV-Vis spectrophotometry were samples A, B, and C containing paracetamol with levels of 5.1667% each; 18.9809%; and 22,9167%.